The Effect of New Spin Wheel Training on Improving Service Technique Skills in The Table Tennis Student Activity Unit - Berlian Gustiarida; Indra Muhamad Safari; Dewi Susilawati (Universitas Negeri Semarang, 2026)
This technique is crucial, but problems arise from insufficient rotation speed, which affects accuracy. In reality, many beginner table tennis players and UKM members still experience difficulties in producing consistent serves, especially with variations in spin and precise ball placement. Observations during the UKM training program indicate that many students struggle to control the ball''s direction, vary its spin, and maintain consistency in their service strokes. This research design uses a quasi-experimental type of research, design the Non-Equivalent Control Design Group is the most frequently used design in social research. This design is where the experimental group is influenced by a particular variable by involving a non-randomly selected control group, measured before and after the intervention. The sample used in this study consisted of 22, the experimental and control groups were divided equally, with 11 participants per variable class. The results of the analysis of covariance (ANCOVA) showed that the covariate variable (pretest) had a significant effect on the posttest score, F (1,39) 8.224 p 0.007. After controlling for the influence of the pretest score, the posttest score experienced a significant difference, F (3,39) 13.605 p 0.001 partial N2 0.511. However, from an inferential perspective, the statistical analysis showed no significant difference between the experimental and control groups (p0.05). This indicates that the effectiveness of the New Spin Wheel method has not been proven strongly at the 5% significance level. This insignificance may be influenced by several methodological factors, including the relatively small sample size, differences in initial ability levels between the groups, and limited control of variables in a quasi-experimental design.